2021
DOI: 10.1039/d1fo00684c
|View full text |Cite
|
Sign up to set email alerts
|

Genistein exhibits therapeutic potential for PCOS mice via the ER-Nrf2-Foxo1-ROS pathway

Abstract: Polycystic ovarian syndrome (PCOS) is a complex endocrinopathy in women of reproductive age and the main cause of female infertility, but there is no universal drug for PCOS therapy. As...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…Melatonin might withhold the expression of FOXO1, whose repression accelerated the defect in the differentiation program in melatonin-treated ESCs, while replenishment of rNOTCH1 ameliorated the impediment of melatonin on FOXO1, but this amelioration was disrupted by NRF2 inhibitor ML385. Moreover, previous study had identified FOXO1 as a direct downstream target of NRF2 [16]. Together these observations suggest that NRF2 acts as downstream of NOTCH1 signaling pathway to mediate the regulation of melatonin on FOXO1.…”
Section: Discussionsupporting
confidence: 61%
“…Melatonin might withhold the expression of FOXO1, whose repression accelerated the defect in the differentiation program in melatonin-treated ESCs, while replenishment of rNOTCH1 ameliorated the impediment of melatonin on FOXO1, but this amelioration was disrupted by NRF2 inhibitor ML385. Moreover, previous study had identified FOXO1 as a direct downstream target of NRF2 [16]. Together these observations suggest that NRF2 acts as downstream of NOTCH1 signaling pathway to mediate the regulation of melatonin on FOXO1.…”
Section: Discussionsupporting
confidence: 61%
“…Meanwhile, genistein increased the levels of Nrf2, which is vital to the GSH system [132][133][134]. Genistein administration induced Nrf2 enhancement by activation/phosphorylation of keap1, sirt1, MAPK-ERK1/2, PKC, and estrogen receptor in other cells or tissues, such as: hippocampal tissue, hypothalamic paraventricular nucleus, ovary, and Caco-2 cells [131,[135][136][137]. However, it is unclear why genistein upregulates the levels of Nrf2 in the myocardium.…”
Section: Glutathione System Activatormentioning
confidence: 99%
“…Indeed, the increased expression of CYP11A1 and HSD3B1 may explain the increased level of P after TP treatment. A possible reason for the increase of the CYP19A1 gene expression is that the abnormal increase of androgens triggers the body's own regulatory mechanism, and by increasing the expression of the CYP19A1 gene, the excess androgen is converted into E 2 [42].…”
Section: Discussionmentioning
confidence: 99%